Territorial distribution of G.I. sheets - Co, Henry C. (1975)
This research paper deals with the planning of a national distribution system. The design of the distribution system was based on the concept of sales territory design, an ordinary management tool in sales administration. For the purpose of experimentation, the case of the G.I. sheets distribution system in the Philippines was studied. Four computer programs, together with scores of subroutine subprograms, all written in FORTRAN IV for the IBM 360 were prepared to facilitate analysis. The results of the computer runs were studied and after thorough analysis of the validity of the results, a set of policies surfaced. Recommendations were then made for these policies.
Thesis (M.S. Industrial Engineering)--University of the Philippines, Quezon City.
Keywords: Iron, Galvanized